PELATIHAN TRANSFORMASI DIGITAL BAGI SISWA DI SMK SWASTA KOLESE TIARA BANGSA KOTA BATAM - Cindoswari, Ageng Rara; Fajrah, Nofriani; Ridho, Muhammat Rasid (PUAN INDONESIA, 2024)
Digital Transformation is now the center of public attention because digital aspects have entered all levels of society, one of which is school students. The use of digital transformation that is not on target will result in misuse of technology and have a negative impact on the person's personal self to others around him. Based on the results of field observations, it is still found that millennials do not pay attention to the considerable impact of digital transformation in their daily lives. Millennials experience the greatest impact, such as not understanding digital literacy but have become actors and users of digital media, resulting in misuse of functions that can even have an impact on criminal and civil acts. This activity was carried out in December 2022 - February 2023. This School Target Development service activity was carried out at SMK Swasta Kolese Tiara Bangsa by providing material on (1). Digital Literacy, (2). Human Interaction with Computers, (3). Interactive Media Design. The results of this activity include (1). Students of SMK Kolese experienced an increased understanding of the importance of digital literacy and communication ethics in social media in the context of human interaction with computers, as well as understanding the basic skills of creative media design, (2). Students of SMK Kolese Tiara Bangsa still need to get technological development literacy to face digital transformation such as how to use ergonomic gadgets so that they still pay attention to health and how to utilize technological sophistication to be able to produce interactive design works such as games, learning media and others. Keywords : Digital Literacy, Computers, Media, Students, SMK Kolese